Exploring the Use of Fanfiction as Authentic Materials in English Language Teaching: A Perspective from a Reading Class - Felicia Cornella Austin; Wulandari Santoso (Prologue: Journal on Language and Literature, 2023)
This research aims to investigate students' perceptions of fanfiction as authentic materials to enhance their reading skills. The participants of this research were 30 students in a state vocational school in Banten. This case study started with the implementation of using Fanfiction in the reading class in five consecutive meetings to give students exposure to Fanfiction stories. During the implementation, reflective notes were used to describe students’ responses towards the use of Fanfictions in relation to their reading skills. Questionnaires consisting of closed and open-ended items were also used to collect data regarding students’ views of the use of Fanfiction in improving their reading skills. Descriptive statistics was used to analyse the quantitative data, while thematic analysis was used to analyse the quantitative data. The results of quantitative and qualitative data analysis showed that the participants showed a positive perception towards the use of fanfiction in enhancing their reading skills although some of the students stated that they had difficulties in understanding the texts due to their lack of vocabulary. The findings of the study could inform pedagogical practices in the classroom that teachers could consider the use of Fanfiction by taking into account students’ needs, interests, and English proficiency.